Nematology in India: The Journey, Perspectives, and a Vision (Indian Journal of Nematology, 2024)
Nematodes are the most numerous, widely distributed and diverse group of multicellular, pseudocoelomate invertebrates with unique morphological and metabolic features with a high degree of adaptations to the trophic and environmental variability. Majority of their species have an important role in regulating the decomposition process and soil health. However, many species of nematodes are parasites of plants and animals, including humans. Nematodes were known to man for several centuries, but nematology as a subject emerged in the beginning of the 20th century in the USA and Europe. The detection of root-knot nematodes in the tea plantations in the Nilgiri hills in 1901 can be said to be the first record of plant parasitic nematodes in India. It was followedby the reports of ufra disease of rice in 1913 and white-tip disease of rice in 1936. In independent India, the zoologists started describing the diverse kinds of plant parasitic and free-living nematodes. The food shortages in the 1950s and 1960s raised big concerns. The discovery of molya disease of wheat and barley by the cereal cyst nematodes in Rajasthan in 1957, and the discovery of the exotic potato cyst nematodes in the Nilgiri hills in 1961 were big concerns. This led to the foundation of Nematology as a separate discipline of plant protection in India in 1966. This article traces the major historical milestones, generational changes and directions in nematology, with special reference to India in fundamental and applied nematology research, education and extension. In spite of the sustained effort of nematologists, nematodes have outsmarted nematologists in most of these areas in practice, not only in India but also in the rest of the world. Failures in truly understanding nematodes and developing dependable management technologies are still lamented. Crop losses and economic impact; development of eco-friendly and economically viable integrated nematode management modules to fit into overall IPM; reliable identification and diagnostic tools; good level of nematode resistance through breeding or molecular techniques; safer nematicides; effective biocontrol agents; use of entomopathogenic nematodes, and understanding the role of nematodes in regulation and prediction of ecosystem function, are still areas that will continue to invite our attention for decades to come. Besides assessing the importance of plant parasitic and entomopathogenic nematodes, the salient achievements made so far, the major limitations, possibilities and a vision for the future are given.